INTEGRASI FISIKA KUANTUM DAN PAI DALAM PEMBINAAN KARAKTER SANTRI - Rohimin Al'Asror; Aria Septi Anggaira; Muhammad Hafidz Khusnadin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In this increasingly complex modern era, the development of santri character has become one of the main focuses in education. This journal presents a discussion on the integration of quantum physics into santri character building in the context of Islamic Religious Education (PAI). Although quantum physics is typically viewed as a scientific discipline separate from religious teachings, this study demonstrates that quantum physics can offer valuable new insights into understanding the spiritual and moral dimensions of life. The methods employed in this research include a qualitative approach and literature analysis that bridges scientific concepts with the values of Islamic Religious Education (IRE). The research findings reveal that integrating quantum physics into the PAI curriculum not only broadens students' thinking but also encourages the application of ethics and moral values in daily life. These findings emphasize that science and spirituality should not be viewed as two conflicting entities, but rather as complementary elements that contribute to the development of intelligent and wise individuals. Thus, the integration of quantum physics into PAI education can train students to think critically, creatively, and prioritize their moral responsibilities, fostering a holistic character.